Rekonstruksi Undang-Undang No. 1 Tahun 1974 (Studi Analisis Hermeneutika Abdullahi Ahmed An-Naim) - Mohammad Koidin (Journal on Education, 2024)
This research will explore Law Number 1 of 1974 concerning Marriage within the framework of Abdullahi Ahmed An-Naim's hermeneutical perspective. By using the library research method from primary and secondary data sources regarding An-Naim's works, the author seeks to present various thoughts from An-Naim. In his thinking, regarding the issue of household leadership, An-Naim states that in Islamic law, changes need to be made to respond to the current situation and conditions. Paternalistic leadership in life is an actual response of Islamic law, so the current situation and conditions also require formulations of legal regulations that have contemporary and applicable spirits in the present time.